Estimates of unintended pregnancy rates over the last decade in France as a function of contraceptive behaviors - Moreau, C. (2013)
OBJECTIVE: We investigate trends in contraceptive behaviors in France and how they may have contributed to fluctuations in unintended pregnancy rates over time and across subgroups of the population between 2000 and 2010. STUDY DESIGN: Data are drawn from 3 national surveys in France, comprising 4714 women ages 15 to 49 in 2000, 8613 in 2005 and 5260 in 2010. We used multinomial and simple logistic regression models to explore trends in contraceptive behaviors over time. We estimated trends in unintended pregnancy rates in relation to population shifts in contraceptive behaviors between 2000 and 2010. RESULTS: A third of women were not using contraception at the time of the surveys. However, only 2.4% in 2000, 3.2% in 2005 and 2.4% in 2010 had an unmet need for contraception (p=0.002). Among contraceptive users, user-dependent hormonal methods decreased from 59% in 2000 to 52% in 2010 (p<0.0001), while long acting reversible methods increased from 22% to 24% (p=0.04). Changes in contraceptive behaviors resulted in fluctuations in unintended pregnancy rates estimated to have risen from 3.16% to 3.49% between 2000 and 2005, and to have decreased to 3.26% in 2010. Small changes in unmet need for contraception exerted the largest effects. CONCLUSION: This study indicates that changes in contraceptive behaviors over the past decade in France have potentially resulted in significant fluctuations in unintended pregnancy rates. Our results also demonstrate that a simple algorithm combining contraceptive behaviors and typical use failure rates may be an acceptable proxy for monitoring trends in unintended pregnancies.